Blockchain-Token: Begriffsabgrenzungen für erfolgreiche Geschäftsmodelle - Carl B. Welker (IU Internationale Hochschule, 2024)
The existence of bitcoins and NFTs, and perhaps also the possibility of founding a company on a blockchain network, should have gotten around after 15 years. At present, software engineers continue to work on solutions in Web3, new business activities such as coin minting, blockchain installations and the creation of Web3-related off-chain and on-chain financial products are constantly being recorded. Major law firms are making all this legally secure for banks, after most extensive legal constructions have been established, lately with Regulation (EU) 2023/1114. In view of all this, it is very surprising that there is still no precise definition of "tokens" from a business and application-oriented perspective. As it stands, the academic field is dominated by computer scientists and, after a few legal conflicts, also by lawyers. The treatment in business and management theory is falling behind. The new Web3 technologies offer considerable potential for companies in all sectors. In order to exploit this potential, the creative options of the new technology must be systematically explored and requirements such as quality and legal certainty must be met when putting them into practice. This requires precise definitions. This discussion paper examines the relevant differentiation criteria of tokens in order to then propose a more precise, selective differentiation of token classes.
Keywords: G30; K12; K22; L14; L15; L26; M13; O17; O32; O33; O35; 650; Web3; Distributed Ledger Technologies; Blockchain; Tokenization; Currency Token; Asset Token; Security Token; Utility Token